Note: Single-polarity high-voltage amplifier to drive coarse-approach slip-stick piezoelectric motors - Belussi, C.H.; Berisso, M.G.; Fasano, Yanina; Fasano, Yanina (AIP Publishing, 2013)
Fil: Belussi, C.H. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina